Depth of response of induction therapy and consecutive maintenance treatment in patients with RAS wild-type metastatic colorectal cancer: An analysis of the PanaMa trial (AIO KRK 0212). (January 2023) - Sommerhäuser, Greta; Kurreck, Annika; Beck, Alexander; Fehrenbach, Uli; Karthaus, Meinolf; Fruehauf, Stefan; Graeven, Ullrich; Mueller, Lothar; Koenig, Alexander O.; v. Weikersthal, Ludwig F.; Goekkurt, Eray; Haas, Siegfried; et al.
Abstract: Background: In patients with RAS wild-type metastatic colorectal cancer, depth of response (DpR) has gained importance as a novel end-point in clinical trials. We investigated the overall DpR, as well as the prognostic and predictive impact of DpR to induction therapy (six cycles of 5-fluorouracil, leucovorin [FU/FA], oxaliplatin [FOLFOX] and panitumumab [Pmab]) on consecutive maintenance therapy (FU/FA plus Pmab or FU/FA alone) in patients treated within the PanaMa trial. Methods: Central radiological assessment was performed according to RECIST 1.1. DpR was defined as percentage change in tumour diameter within defined time intervals (induction therapy, maintenance therapy, total course of therapy). For prognostic and predictive analyses, median DpR (</≥) served as threshold. Results: Out of 248 patients receiving maintenance therapy, 211 were evaluable for DpR analyses (FU/FA + Pmab, n = 106; FU/FA alone, n = 105). The overall DpR in all patients was 56.5%. DpR of induction therapy (42.5%) accounted for the largest proportion (75.2%) of the overall DpR. While greater DpR to induction therapy was significantly associated with prolonged PFS (HR 0.70, 95% CI 0.52–0.93, p = 0.013) and OS (HR 0.38, 95% CI 0.28–0.51, p < 0.001), there was no significant correlation of DpR and maintenance treatment arm. Conclusions: In the PanaMa trial, the overall DpR was similar to DpR achieved by other epidermal growth factor receptor-based regimens. DpR to induction therapy accounted for three quarters of the total tumour shrinkage potentially suggesting that FOLFOX plus Pmab can be de-escalated following induction without substantially compromising efficacy. DpR to induction therapy was prognostic but not predictive for efficacy of consecutive maintenance therapy. Clinical trial information: NCT01991873. Graphical abstract: Image 1 Highlights: In the PanaMa trial, the median overall DpR was 58.1% versus 54.9%, respectively. Approximately 75% of the overall DpR was achieved during induction therapy. Additional DpR achieved by maintenance therapy was numerically greater with Pmab. DpR to induction was prognostic for PFS and OS of maintenance therapy.